Effect of staining and whitening systems on color stability of computer aided design/computer aided manufacturing lithium disilicate glass ceramic - Nadia S. Al-Angari; Shahad Quwayhis; Nouf Almayouf; Shahad Meaigel; Abdulelah Aldahash; Sarah S. Al-Angari (Elsevier, 2023)
Purpose: To investigate the effect of coffee stain and whitening systems on the color stability of CAD/CAM glazed lithium disilicate glass-ceramics (LDGCs). Methods:  68 glazed LDGC discs (12 × 10 × 2 mm) were fabricated using blocks of CAD/CAM systems (IPS e.max CAD ceramic). Baseline color was measured (CIE/L*a*b*), and specimens were randomized into four groups (n = 17). All specimens were stained (coffee solution; 24 h/d × 12) and then subjected to two whitening protocols. G1- (kept moist × 7 days); G2-positive control (brushed with distilled water, 200gm/load, 2 min twice daily × 7 days); G3- whitening toothpaste (Colgate optic white; relative dentin abrasivity = 100, 200gm/load, 2 min twice daily × 7 days) and G4-simulated at-home bleaching protocol (Opalescence,15% carbamide peroxide (CP), 6 h/day × 7 days). The study outcome was color change (ΔE) measured at baseline, after staining, and after whitening treatments. Data were analyzed using paired T-test and one-way ANOVA (α = 0.05). Results: All groups stained equally (p > 0.05) but were not clinically significant (ΔE ≤ 1.05). Stains were significantly (p ≤ 0.01) improved in G2 and G3 (ΔE = 0.69 and 0.63), yet were not eliminated compared to bleaching, which had the highest color improvement and completely removed the stains (ΔE = 0.72). Conclusions: Glazed LDGC was color stable after simulating one year of coffee staining. Bleaching, using 15% CP for a week, completely removed the stains and returned the LDGCs to their original shade. However, simulating eight months of brushing, regardless of the toothpaste content, improved the color outcome but didn't remove it completely.